Hubungan Media Informasi, Pengetahuan, Pendidikan, Pengalaman Dengan Tingkat Kecemasan Masyarat Di Massa Pandemi Covid-19 - Achmad Masfi; Miftahul Arifin (Jurnal Keperawatan Muhammadiyah, 2022)
The virus was first detected in Indonesia on March 2, 2020 and announced by President Joko Widodo, which caused anxiety. The purpose of this study was to analyze the relationship between information media, knowledge, education, experience, stigma and public anxiety during the covid 19 pandemic.The type of research used in this study is "Analytic Correlative with a Cross Sectional approach." Analytic Correlative means that the research aims to perform a correlative analysis between variables. With a research sample of 213 respondents. With independent variables media information, knowledge, education, and experience, while the dependent is the level of anxiety. For statistical test on bivariate using Spearman rank and chi-square and statistical test on multivariate using ordinal regression statistical test.The results of this study were obtained, more than half of the information media supported as many as 141 (66.2%) respondents, Knowledge of more than half was good as many as 143 (67.1%) respondents, Education was more than half with high school education level as many as 121 (56.8%) respondents, Experience more than half of the experienced community as many as 139 people with a percentage (65.3%), Anxiety more than half of them do not experience anxiety or normal as many as 120 people with a percentage (56.3%) of respondents.Which this result it is sugested that the next researcher examines other specific variabels of public anxiety. So, it can be used as a reference in handling public anxiety during the covid-19 pandemic.Key word: Anxiety, Information media, Knowledge, Education, experience, covid-19